Gains in sustainability using Voluntary Sustainability Standards: A systematic review - Kairo Fernandes Martins; Denilson Teixeira; Rogério de Oliveira Corrêa (Cleaner Logistics and Supply Chain)
The ongoing growth of concerns with regard to the sustainability of the planet has led to the increasing expansion on international agendas of commercial certification schemes based on Voluntary Sustainability Standards (VSSs). This has influenced public planning and policy-making, and stimulated the interest of researchers. The application of VSSs plays an important role in the transition of supply chains toward sustainability. These initiatives promote appropriate social, economic, and environmental practices for the production of goods and services, as well as meeting the demands of environmentally-conscious consumers. However, the diverging definitions of the concept, and the contradicting interpretations of the impacts of VSSs exacerbate the complexity of the analysis of their real impacts on Global Value Chains. The present study is based on a systematic review of the literature on VSS based on the Systematic Search Flow method. The principal objectives of the study were to identify the prevailing groups of researchers on the VSS theme and their perceptions regarding the sustainable gains with the adoption of these standards. A number of different terms have been used in the literature on standards, although “Voluntary Sustainability Standards” has been consolidated by its use in recent years, and provides a focal point for the analysis of standards of sustainability. Two different streams of thought were identified here. These streams complement each other. The first considers VSSs to be a barrier to the access of producers to major consumer markets, while the second stream of thought argues that VSSs fulfill, stimulate, and objectify sustainability. The results of the review show that the gains of adopting a VSS are diverse, with the economic pillar being the most valued, in general. Based on the distinct pillars of sustainability, our analysis contributes to a robust and differentiated understanding of the topic of VSS by identifying an ample range of examples that consider the gains in sustainability accruing to the application of VSSs. The analysis also establishes valuable insights and guidelines for the expansion of research in this field.